Benzoato bridged dinuclear Mn(II) and Cu(II) compounds involving guest chlorobenzoates and dimeric paddle wheel supramolecular assemblies: Antiproliferative evaluation and theoretical studies. (1st November 2021) - Sharma, Pranay; Dutta, Debasish; Gomila, Rosa M.; Frontera, Antonio; Barcelo-Oliver, Miquel; Verma, Akalesh K.; Bhattacharyya, Manjit K.
Graphical abstract: In vitro antiproliferative activities of benzoato bridged dinucler Mn(II) and Cu(II) compounds involving enclathrated guest chlorobenzoates and dimeric paddle wheel supramolecular assemblies. Abstract: Two new benzoato bridged Mn(II) and Cu(II) dinuclear coordination compounds viz. [Mn2 (bipy)2 (4-Clbz)2 (H2 O)4 ]2(4-Clbz) (1 ) and [Cu2 (bz)4 (2-MePy)2 ] (2 ) (bipy = 2, 2́-bipyridine, 4-Clbz = 4-chlorobenzoate, bz = benzoate, 2-MePy = 2-methylpyridine) have been synthesized and characterized using elemental analysis, TGA, spectroscopic (FTIR, electronic, EPR) and single crystal X-ray diffraction techniques. Crystal structure analysis of compound 1 reveals the enclathration of guest 4-Clbz moiety in the supramolecular host tetramer which provides rigidity to the crystal structure. Further analysis reveals the presence of cooperative (π–π)2 /(π–π)1 /(π–π)2 ternary assemblies involving alternate coordinated and uncoordinated 4-Clbz moieties. In compound 2, intermolecular CH∙∙∙O, CH∙∙∙π and CH∙∙∙C contacts are involved in the formation of dimeric paddle wheel supramolecular assemblies which stabilizes the layered architecture. The cooperative interplay of H-bonding and π-stacked ternary assemblies of 1 has been studied theoretically using DFT calculations, MEP surface and NCI Plot computational tools. The large interaction energies along with the NCI plot index analysis confirm that the π-stacking assemblies in combination with the H-bonds are strong binding motifs. In vitro anticancer activity of the compounds considering cytotoxicity and apoptosis assays reveal significant concentration dependent cytotoxicity in Dalton's lymphoma (DL) cancer cell lines with nominal effects in normal healthy PBMC cells. Molecular docking study reveals the efficient interaction of the compounds with the antiapoptotic BCL family target proteins.